Tajdied Method Implementation in Improving The Quality of Tahfidz Al-Quran Juz 30, 29, and 1 In Sd Muhammadiyah 10 Surabaya - Ahmad Munhamir (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Memorizing the koran now feels so easy with various methods that adopt changes in people's lifestyles. This is very encouraging so that it is not only dominated by pesantren circles, but all circles can become memorizers as long as there is intention and sincerity. The formulation of the problem of this thesis, First, how is the development of the potential and quality of tahfidz. Second, how to implement the tajdied method in supporting the quality of memorization. Third, what are the supporting and inhibiting factors of implementing the tajdied method in memorizing koran juz 30, 29, and 1 at SD Muhammadiyah 10 Surabaya. This research is included in the qualitative category, data collection using participant observation, interviews, and documentation, using data reduction, presentation, and verification. The results showed that: the learning process uses one day one maqro' hijaz. Implementation of activities: memorizing deposits, murajaah, munaqosah, and grand graduation. Supporting factors were found: using the rasm ustmani quran equipped with maqro' hijaz markers, murottal hijaz tutorials in various forms, such as youtobe, MP4, MP3, as well as discussion groups via social media, level memorization targets, awards, time management, and virtual munaqosah (at during the Covid-19 pandemic). Inhibiting factors: there is no complete series of koran rasm ustmani with hijaz tone markers, boredom during the Distance Learning period, lack of ability to manage time between school assignments and memorization, weak family and social environment motivation, uncomfortable home environment conditions, and limited internet quota.